Proceedings of the Mathematics, Informatics, Science, and Education International Conference (MISEIC 2019) 2019
DOI: 10.2991/miseic-19.2019.8
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of Invertebrates in Kemantren Coast, Lamongan

Abstract: Kemantren beach is located in the Kemantren Village, Paciran District, Lamongan Regency. This beach is consists of sand and coral substrate. Kemantren beach is one of the small coastal islands of Java that has already reclaimed with spot of high ecotourism potency and habitat for numerous types of invertebrate. Unfortunately, there were no previous records about invertebrate biodiversity in this area. The purpose of this research was to identify various invertebrate species inhabiting Kemantren beach, Lamongan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Few papers describe research on the macrozoobenthos of the main island of Java. Five publications describe echinoderms, mollusks, and benthic invertebrate diversity off the island's northern coast (Putri et al, 2019;Rahayu et al, 2019;Elfahmi and Efendy, 2020;Sabdono et al, 2021;Atlanta et al, 2022). Other reports describe mainly echinoderms and mollusks in Baluran National Park (Huda et al, 2017;Setiawan et al, 2019a, Setiawan et al, 2019b and in the Situbondo (Sari and Aunurohim, 2013;Somma et al, 2017), of the island's eastern coast (R5).…”
Section: Records Of Research On the Macrozoobenthos In Java Coral Reefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few papers describe research on the macrozoobenthos of the main island of Java. Five publications describe echinoderms, mollusks, and benthic invertebrate diversity off the island's northern coast (Putri et al, 2019;Rahayu et al, 2019;Elfahmi and Efendy, 2020;Sabdono et al, 2021;Atlanta et al, 2022). Other reports describe mainly echinoderms and mollusks in Baluran National Park (Huda et al, 2017;Setiawan et al, 2019a, Setiawan et al, 2019b and in the Situbondo (Sari and Aunurohim, 2013;Somma et al, 2017), of the island's eastern coast (R5).…”
Section: Records Of Research On the Macrozoobenthos In Java Coral Reefsmentioning
confidence: 99%
“…All studies in this region were conducted at Kepulauan Seribu; Mollusca predominated (161 species), followed by Echinodermata (74 species), Arthropoda (30 species), and Platyhelminthes (1 species). Four phyla and 99 species were reported to occur off the northern coast of East Java (R4), with the largest contribution derived from the biodiversity research conducted by Rahayu et al (2019) in the Lamongan coastal area. The most diverse taxa were Mollusca (69 species), followed by Echinodermata (15 species), Crustacea (11 species), and Platyhelminthes (4 species).…”
Section: Macrozoobenthic Species Richness and Compositionmentioning
confidence: 99%
“…Research conducted by (Hidayah and Ambarwati 2020) showed that the bivalves found in the intertidal zone of the coast of Boom Beach, Tuban consisted of 13 species dominated by Tellina timorensis. Another study conducted by Rahayu et al (2019) showed that the bivalves found in Kemantren Beach, Paciran, Lamongan consisted of six families, namely Cardidae, Veneridae, Arcidae, Cardiidae, Isognomonidae, dan Arcidae. Another study conducted by Zarkasyi et al (2016) showed that the Coastal Coast of Ujung Pangkah, Gresik, was dominated by Meretrix meretrix yellow, M. lamarckii, and Paphia undulata.…”
Section: Introductionmentioning
confidence: 99%
“…Few papers describe research on the macrozoobenthos of the main island of Java. Five publications describe echinoderms, mollusks, and benthic invertebrate diversity off the island's northern coast (Putri et al, 2019;Rahayu et al, 2019;Elfahmi and Efendy, 2020;Sabdono et al, 2021;Atlanta et al, 2022). Other reports describe mainly echinoderms and mollusks in Baluran National Park (Huda et al, 2017;Setiawan et al, 2019a, Setiawan et al, 2019b and in the Situbondo (Sari and Aunurohim, 2013;Somma et al, 2017), of the island's eastern coast (R5).…”
Section: Records Of Research On the Macrozoobenthos In Java Coral Reefsmentioning
confidence: 99%
“…All studies in this region were conducted at Kepulauan Seribu; Mollusca predominated (161 species), followed by Echinodermata (74 species), Arthropoda (30 species), and Platyhelminthes (1 species). Four phyla and 99 species were reported to occur off the northern coast of East Java (R4), with the largest contribution derived from the biodiversity research conducted by Rahayu et al (2019) in the Lamongan coastal area. The most diverse taxa were Mollusca (69 species), followed by Echinodermata (15 species), Crustacea (11 species), and Platyhelminthes (4 species).…”
Section: Macrozoobenthic Species Richness and Compositionmentioning
confidence: 99%